Assessing the Impact of the Assimilation of SWOT Observations in a Global High-Resolution Analysis and Forecasting System Part 1: Methods - Benkiran, Mounir; Ruggiero, Giovanni; Greiner, Eric; Le Traon, Pierre-Yves; Rémy, Elisabeth; Lellouche, Jean Michel; Bourdallé-Badie, Romain; Drillet, Yann; Tchonang, Babette (Frontiers in Marine Science, 2021)
The future Surface Water Ocean Topography (SWOT) mission due to be launched in 2022 will extend the capability of existing nadir altimeters to enable two-dimensional mapping at a much higher effective resolution. A significant challenge will be to assimilate this kind of data in high-resolution models. In this context, Observing System Simulation Experiments (OSSEs) have been performed to assess the impact of SWOT on the Mercator Ocean and Copernicus Marine Environment Monitoring Service (CMEMS) global, high-resolution analysis and forecasting system. This paper focusses on the design of these OSSEs, in terms of simulated observations and assimilation systems ocean model and data assimilation schemes). The main results are discussed in a companion paper. Two main updates of the current Mercator Ocean data assimilation scheme have been made to improve the assimilation of information from SWOT data. The first one is related to a different parametrization of the model error covariance, and the second to the use of a 4D version of the data assimilation scheme. These improvements are described in detail and their contribution quantified. The Nature Run used to represent the “truth ocean” is validated by comparing it with altimeter observations, and is then used to simulate pseudo-observations required for the OSSEs. Finally, the design of the OSSEs is evaluated by ensuring that the differences between the assimilation system and the Nature Run are statistically consistent with the misfits between real ocean observations and real-time operational systems.